Pengaruh Literasi Keuangan Syariah, Kemudahan, Dan Kepercayaan Terhadap Minat Mahasiswa Keuangan Dan Perbankan Syariah Politeknik Negeri Medan Menggunakan Byond by BSI - Putri Hadi Utami; Diena Fadhilah; Marlya Fatira; Rahmadani; Muhammad Zuardi (Jurnal Ekonomi Syariah Pelita Bangsa, 2026)
This study examines the interest of students of the Islamic Finance and Banking Study Program at Medan State Polytechnic in using BYOND by BSI. There are three independent variables in this study: Islamic financial literacy, convenience, and trust; the dependent variable is interest. Normality, heteroscedasticity, multicollinearity, and autocorrelation tests are prerequisite tests. The results of the partial test indicate that the Islamic financial literacy variable partially has a moderate and significant positive effect on interest in using BYOND by BSI with a significance level of 0.022, the convenience variable partially has a strong positive effect on interest in using BYOND by BSI with a significance level of 0.054, and the trust variable partially has a very strong and significant positive effect on interest in using BYOND by BSI with a significance level of 0.000. With a significance level of 0.000, the interest of students in the Islamic Finance and Banking Study Program at the Medan State Polytechnic is positively and significantly influenced by the variables of Islamic financial literacy, ease, and trust in using BYOND by BSI.